Assembling graphene aerogel hollow fibres for solar steam generation. (November 2022) - Li, Guangyong; Fang, Dan; Hong, Guo; Eychmüller, Alexander; Zhang, Xuetong; Song, Wenhui
Abstract: Solar vapor generation, a cost-effective way to harvest solar energy for purifying polluted or saline water, has attracted great attention in recent years. However, during the harsh environment (e.g. high-salinity brine), challenges still remain in limited water evaporation, complicated/compromised systems between water transport, evapor area and salt accumulation. Herein, graphene aerogel hollow fibers (GAHF) are developed and assembled into a solar steam generator which demonstrates exceptionally high efficiency for water evaporation and salt rejection under sun irradiation. Inspired from the capillary water transportation system in trees, the mesophase-ordered GAHFs are spun from their liquid crystalline suspension, and subsequently assembled into a roll of unidirectionally aligned bundles and then embedded in a transparent polydimethylsiloxane (PDMS) matrix. The synergistic effects between GAHFs, serving as 1D-confining micro-channels for water transport and broadband solar absorbers, and PDMS matrix, as an light refractor and "canyons"-like evaporation area, improve the water flow and absorption of solar energy and maximize the evaporation surface area. As a result, the GAHF arrays expedite remarkable transpiration, achieving continuous steam generation (∼3.29 kg m −2  h −1 ) and outstanding salt-rejection performance for high-salinity brine (e.g. saturated solution) desalination. This GAHF based solar steam generation system provides a facile and high-performance device for self-generating seawater desalination. Graphical abstract: Image 1 Highlights: The GAHFs were fabricated by co-axial dynamic sol-gel spinning with subsequent reduction and supercritical drying。. An aligned GAHF array with exceptional high efficiency for water evaporation and salt rejection irradiation was developed. The GAHF roll based solar steam generation system expedited remarkable transpiration with salt-rejection performance.